2021
DOI: 10.1080/2000656x.2021.1953042
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytes are larger in lymphedematous extremities than in controls

Abstract: Lymphedema is caused by dysfunctional lymph vessels or as a complication of cancer treatment leading to edema and adipose tissue deposition. One hypothesis is that adipocyte hypertrophy contributes to the volume increase in lymphedema. The aim of the study was to compare adipocyte size in arm and leg lymphedema and controls. The adipocyte size difference was also compared between the arms and legs. Furthermore, any link between adipocyte size difference and gender, lymphedema onset, duration, previous radio-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…It is well established that an increased deposition and remodeling of adipose tissue characterized by hypertrophy occurs in the early years of lymphedema onset [ 18 ]. These clinical observations, as reported by Zhang et al [ 19 ], have been further confirmed in lymphedema experimental models—defined as increased lipid content and the expression of adipogenesis-related genes [ 20 , 21 ].…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…It is well established that an increased deposition and remodeling of adipose tissue characterized by hypertrophy occurs in the early years of lymphedema onset [ 18 ]. These clinical observations, as reported by Zhang et al [ 19 ], have been further confirmed in lymphedema experimental models—defined as increased lipid content and the expression of adipogenesis-related genes [ 20 , 21 ].…”
Section: Resultssupporting
confidence: 59%
“…A number of well-known histological hallmarks were identified in the lymphedematous tissue. First of all, increased epidermal thickness was identified in the edematous tissue [ 17 , 19 , 26 ], which is used as a primary outcome measure for the efficacy of lymphedema treatments, such as the anti-inflammatory drug ketoprofen or anti-Th2 immunotherapy [ 10 , 27 ]. Fibrosis, a well-known hallmark and key driver of lymphedema, was significantly increased in the lymphedematous adipose tissue, but to our surprise, increased collagen deposition was noted in the non-lymphedematous tissue as well.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al also reported that the size of adipocytes from lymphedema extremities was greater than that from normal extremities. 33 The increase of oil red O amount was attributable to the increase in the size of adipocytes, not the number of adipocytes by proliferation from ASCs. ASCs with lymph culture resulted in increased cell differentiation rather than cell proliferation.…”
Section: Discussionmentioning
confidence: 95%
“…T-cell inhibition/depletion of CD4+ cells decrease the severity of lymphoedema in obese animals [9,34,35]. The human lymphoedema fat tissue appear different compared to normal adipose tissue, with 24% larger [36] and highly variable adipocytes in size [10] compared to adipose tissue. Larger lobules, more collagen and a decreased number of M2 macrophages is also seen in lymphoedema adipose tissue [10].…”
Section: Discussionmentioning
confidence: 99%